Introduksi Diversifikasi Olahan Ikan Nila Untuk Masyarakat Di Kecamatan Kawali, Kabupaten Ciamis, Jawa Barat - Pramono Adi (indonesia), Catur; Juliana Napitupulu (indonesia), Romauli (JURNAL KASTARA, 2024)
All cadets in the Fishery Product Processing Engineering and Fish Cultivation study programs participated in Community Service Activities (PKM), with the goal of understanding, adapting, and identifying various activities in the cultivation and processing areas in order to train themselves before entering the workforce. The goals of this PKM activity are to learn about the characteristics of the Nila Village cultivation and processing area, Banjarwaru Hamlet, Kawali District, Ciamis Regency, as well as the social and economic income activities of the Nila Village cultivating and processing community. According to the findings of this activity, the types of fish processing businesses in Nila Kawali Village are jellyfish products, kurucuk, gemil noodles, tilapia ice cream, and tilapia fish sticks; POKLAHSAR business activities do not have fixed income and expenses because products are processed as orders are received; and all products do not have a long shelf life because they do not contain preservatives.